Scanning Electron Microscopy Morphology Failure Analysis of Rattan Fibers - Saion, Mohamad Pazlin bin; M.Y, Yuhazri; M.H, Amirhafizan (Universitas Mercu Buana, 2022)
Today, rattan yarns are developed in the furniture industry because they are readily available, inexpensive, harmless to health, and biodegradable to the environment; hence, by utilizing it as a hybrid composites fibre, it will be able to resolve the environmental problem in the future [1,2]. The development of rattan yarns as composite materials is quite well recognized, considering the availability of natural fiber (rattan) raw materials in Malaysia and Southeast Asia. This study was carried out to get a technical examination of the tensile strength of rattan yarns fibre compounds using polyester resin as the matrix. The goal of this experiment is to define the tensile strength composite of rattan yarns fibres that influences the diameter of the fibres from 1 mm to 5 mm maximum. For varied angles of cross section area, single fibre bundles were studied using a scanning electron microscope for fractography study, which revealed comparably heterogeneous breaks linked with additional existence of microfibrils. Tensile tests were executed at diverse diameters (1–5 mm) while tensile speed consistently at 100 mm/min to assess the effects of diameter and gauge length on tensile properties. The tensile strength (26.972 MPa) and Young’s modulus (1761.444 MPa) of rattan yarn fiber at 5 mm width revealed the utmost rate related to the others. The tensile strength and Young’s modulus augmented with the rise of width of rattan fiber bundles.